Bipolar Affective Disorder In 10year Old Boy: A Case Report On Mania - Dr Shilpa; Dr Vikas Kumar; Dr Seikhoo Bishnoi (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Bipolar disorder in children often goes unrecognized due to various factors such as lack of awareness, diagnostic confusion, and unique clinical presentations. This case report details the clinical course of Mr. X, a 10-year-old male diagnosed with bipolar mania. The symptoms, treatment with olanzapine and valproate, prognosis upon discharge, and follow-up are discussed.Differential diagnoses of attention-deficit/hyperactivity disorder, conduct disorder and dissociative disorder were considered but eliminated.